Chronic axillary web syndrome: 83 months post lumpectomy-A Case report - Laura F Rezende; Ricardo Laier Franco; Vanessa Fonseca Vilas Boas; Juliana Lenzi; Regiane Luz Carvalho (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Introduction: Axillary Web Syndrome (AWS) is well described until 3 months postoperative breast cancer surgery.  Methods: We report a case of a 47 years old patient that arrived our rehabilitation service with pain and limited shoulder range of movement in the ipsilateral side of a breast cancer surgery.  Results: An Axillary Web Syndrome was diagnosed 83 months after the surgery.  Conclusion: It is important to mention that AWS might persist for a long time and also affect patients a long time after the surgery.